DASH diet recipes visualizer / Noormufarrina Jhannah Rosli - Rosli, Noormufarrina Jhannah (2019)
DASH diet stands for Dietary Approaches to Stop Hypertension and it is recommended for people who want to lower their high blood pressure. A lot of DASH diet recipes are available on the Internet for people who want to follow the diet. However, the recipes are only represented in text forms that are static and non-interactive where people must read line by line to gain underlying information which can be time-consuming. Therefore, the purpose of this project is to visualize the ingredients of DASH diet recipes interactively to show the ingredients of the recipes based on the main food groups of the food pyramid. DASH diet recipes and list of foods for the main food groups are collected from the Internet and pre-processed by using Python library which is the Natural Language Toolkit (NLTK) to perform lemmatization. Then, the ingredients of the recipes are identified into Grains, Protein, Fats, Oils and Sugar, Fruits, Vegetables, Milk and Dairy and Others by comparing the ingredients with the list of food for each food group. The result of the analyzation is stored in JSON files and the JSON files are implemented in the Circle Packing algorithm to generate interactive visualization of the recipes. The tool used to create the interactive Circle Packing visualization is D3. Functional testing is done to evaluate the functionality of the visualization application and the result shows that the visualization application works accordingly. This project will be beneficial for people to gain quick information in an interactive and fun way. It provides a new kind of way to convey information about recipes.